2019
DOI: 10.1287/isre.2018.0803
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Information Technology and Other Investments: A Contingent Interaction Model

Abstract: Recent studies on the business impacts of information technology (IT) have examined these impacts in the context of either other organizational resources or contingency factors. In this study we integrate these perspectives to develop a contingent interaction model. This model examines how a firm’s IT investment interacts differently with resources focusing on creating value (i.e., R&D) and resources focusing on value appropriation (i.e., advertising), depending on the environmental turbulence in the firm’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…Our stock market-based performance measures can be affected by other organizational strategies in addition to advertising productivity. We therefore included six control variables, informed by related finance and marketing studies (Feng, Morgan and Rego, 2017;Havakhor et al, 2019;Sridhar, Narayanan and Srinivasan, 2014). Earlier studies have demonstrated that performance varies based on firm size (Dang, Li and Yang, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our stock market-based performance measures can be affected by other organizational strategies in addition to advertising productivity. We therefore included six control variables, informed by related finance and marketing studies (Feng, Morgan and Rego, 2017;Havakhor et al, 2019;Sridhar, Narayanan and Srinivasan, 2014). Earlier studies have demonstrated that performance varies based on firm size (Dang, Li and Yang, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…We posit that these three market conditions will impact the nexus between advertising productivity and an organization's financial performance. Market dynamism denotes the frequency, extent and unpredictability of changes that marketplaces undergo (Havakhor et al, 2019;Qu, Pinsoneault and Oh, 2011;Xue, Ray and Sambamurthy, 2012). Market dynamism brings about changes in customer preferences and attitudes, and the development and introduction of new products, innovative technology or competition (Qu, Pinsoneault and Oh, 2011).…”
Section: The Moderating Role Of Market Conditionsmentioning
confidence: 99%
“…The firms selected for this study are large US-based public firms where the leadership structure is very clear, hence the issues of principal-agent are salient. (1990)(1991)(1992)(1993) and 2006 Fortune Global 1000 firms while Havakhor et al (2019) used a longitudinal data from 1999 to 2008 to study the interaction effects of IT and other investments. The data set for this study was gleaned from the LexisNexis Academic wire index.…”
Section: Methodsmentioning
confidence: 99%
“…IS investment is measured differently in the reviewed literature, more specifically in the longitudinal empirical research. IS annual budget (also known as IS spending, IS expenditures) (e.g., Baker et al, 2008;Havakhor et al, 2019;Peslak, 2003;Walsh et al, 2010) is the most frequently used variable to measure the magnitude of IS investment. Other approaches include IS capital (e.g., Barua et al, 1995;Kleis et al, 2012;Tam, 1998), IS capital scaled to total assets (e.g., Chowdhury, 2006;Dewan & Ren, 2011;Xue et al, 2012), IS budget scaled to sales or revenue (e.g., S. Aral & Weill, 2007; J. K. Kim et al, 2009;Mithas et al, 2016), IS budget scaled to total operating costs (e.g., Thouin et al, 2008), IS budget per employee (e.g., Mithas et al, 2012;Ray et al, 2005), and IS capital per employee (e.g., Bloom et al, 2012).…”
Section: Is Measuresmentioning
confidence: 99%